SIKAP DAN KINERJA BANK TABUNGAN NEGARA (BTN) TERHADAP RESPON HASIL SURVEI KEPUASAN KONSUMEN UNTUK MENINGKATKAN LOYALITAS NASABAH DI BALI (Studi Kasus Pada Kantor BTN Cabang Denpasar) - I Dewa NyomanUsadha; Ni Luh Ketut Ayu Sudha Sucandrawati; Kadek Diantara Adi Putra (Universitas Mahendradatta, 2023)
The achievement of consumer loyalty is the company's advantage to beable to survive in increasingly fierce competition. Loyal bank customers have thepossibility to provide recommendations to other customers. This study focuses onthe competencies, attitudes and performance of employees to the responses tocustomer satisfaction survey results to increase customer loyalty at the DenpasarBranch of the Bank Tabungan Negara. Data were collected using a questionnaireusing 100 samples of respondents which were then processed using path analysis.Based on the analysis results obtained that attitude has a significant effect oncustomer loyalty, performance, has no significant effect on customer loyalty,satisfaction, has a significant effect on customer loyalty, attitude has a significanteffect on satisfaction, performance has no significant effect on satisfaction andattitudes and performance are mediated by satisfaction consumers influence oncustomer loyalty. So that recommendations can be given to the Denpasar Branchof the Bank Tabungan Negara to always provide the best service for eachcustomer appropriately and responsively so that employee performance has amore positive impact on customer satisfaction and loyalty.